Developing and validating a model for assessing paid mobile learning app success. Issue 4 (19th May 2019) - Wang, Yu-Yin; Wang, Yi-Shun; Lin, Hsin-Hui; Tsai, Tung-Han
ABSTRACT: With the proliferation of paid mobile learning applications (m-learning apps), understanding how to assess their success has become an important issue for academics and practitioners. Based on the information systems (IS) success models and the value-based adoption model, this study developed and validated a multidimensional model for assessing paid m-learning app success. The proposed model describes the interrelationships among seven paid m-learning app success variables: system quality, information quality, perceived enjoyment, perceived fee, user satisfaction, intention to reuse, and learning effectiveness. Data collected from 160 paid m-learning app users were tested against the research model using structural equation modeling (SEM). The empirical findings provide evidence that learning effectiveness is affected by user satisfaction and intention to reuse, which, in turn, are determined by system quality, information quality, perceived enjoyment, and perceived fee. The findings of this study provide several important theoretical and practical implications for the development, implementation, and promotion of paid m-learning apps.